Behaviour and design of hybrid RC beam-to-steel column connections. (1st January 2022) - Moharram, M.I.; Bompa, D.V.; Xu, B.; Elghazouli, A.Y.
Highlights: hybrid connections between steel columns and RC beams through shear-keys are considered. detailed nonlinear numerical assessments employing concrete damage plasticity models. validation of numerical procedures against a series of tests on hybrid specimens. over 200 three-dimensional numerical parametric simulations on hybrid connections. the main mechanisms governing the ultimate response are quantified. simplified procedures and expressions are proposed for the design of critical regions. Abstract: This paper deals with the performance and design of hybrid connections between steel columns and RC beams by means of shear-keys, through detailed nonlinear numerical assessments in which the influence of key geometric and material parameters on the ultimate behaviour is examined. The numerical simulations employ concrete damage plasticity modelling and procedures which are validated against test results on hybrid members. Extensive parametric assessments involving over two hundred three-dimensional models are carried out, with focus on the effects of varying the shear-key embedment length and section size, longitudinal and transverse reinforcement ratios, concrete strength, and cross-section size. The numerical results enable an in-depth understanding of the main mechanisms governing the ultimate response which can occur in shear, flexure, crushing of a direct strut at the steel-to-concrete interface, or yielding of the shear-key at the column face. Based on the findings from the numerical assessments coupled with test observations, procedures and expressions are proposed for the design of critical regions and of the shear-key. The suggested design expressions are shown to provide reliable predictions across a wide range of shear-key length-to-depth ratios, thus offering a simple method suitable for the application of hybrid connections with shear-keys in design practice.